The The Effect of Emotional Intelligence and Work Life Balace on Job Satisfaction at PT. Kumala Motor Cemerlang Manado - Damaris Yunika Pinangkaan; Maryam Mangantar; Maria V. J Tielung (Universitas Sam Ratulangi, 2022)
Job satisfaction is an affective or emotional response to various aspects or aspects of a person's job so that job satisfaction is not a single concept. A person can be relatively satisfied with one aspect of a job and dissatisfied with one or more other aspects. Job Satisfaction is a worker's (positive) attitude towards his job, which arises based on an assessment of the work situation. The assessment can be carried out on one of the jobs, the assessment is carried out as a sense of appreciation in achieving one of the important values in the job. Satisfied employees prefer their work situation rather than dislike them. The objectives of this study are to determine the effect of Emotional Intelligence and Work Life Balance simultaneously or partially have a significant effect on Job Satisfaction At PT. Kumala Motor Cemerlang Manado. The analytical method used is multiple linear regression. The results of the hypothesis test found that simultaneously Work Life Balance and Emotional Intelligence had a significant effect on Job Satisfaction at PT. Kumala Motor Cemerlang Manado., but partially Work Life Balance has no significant effect on Job Satisfaction at PT. Kumala Motor Cemerlang Manado. For PT. Kumala Motor Cemerlang Manado to maintain and improve the quality of Emotional Intelligence so that employees who work can be more satisfied and can help improve the quality of their performance later